Genomic and phenotypic comparison of two variants of multidrug-resistant Salmonella enterica serovar Heidelberg isolated during the 2015–2017 multi-state outbreak in cattle - Burciaga, Selma; Trachsel, Julian M.; Sockett, Donald; Aulik, Nicole; Monson, Melissa S.; Anderson, Christopher L.; Bearson, Shawn M. D. (Frontiers in Microbiology, 2023)
Salmonella enterica subspecies enterica serovar Heidelberg (Salmonella Heidelberg) has caused several multistate foodborne outbreaks in the United States, largely associated with the consumption of poultry. However, a 2015-2017 multidrug-resistant (MDR) Salmonella Heidelberg outbreak was linked to contact with dairy beef calves. Traceback investigations revealed calves infected with outbreak strains of Salmonella Heidelberg exhibited symptoms of disease frequently followed by death from septicemia. To investigate virulence characteristics of Salmonella Heidelberg as a pathogen in bovine, two variants with distinct pulse-field gel electrophoresis (PFGE) patterns that differed in morbidity and mortality during the multistate outbreak were genotypically and phenotypically characterized and compared. Strain SX 245 with PFGE pattern JF6X01.0523 was identified as a dominant and highly pathogenic variant causing high morbidity and mortality in affected calves, whereas strain SX 244 with PFGE pattern JF6X01.0590 was classified as a low pathogenic variant causing less morbidity and mortality. Comparison of whole-genome sequences determined that SX 245 lacked ~200 genes present in SX 244, including genes associated with the IncI1 plasmid and phages; SX 244 lacked eight genes present in SX 245 including a second YdiV Anti-FlhC(2)FlhD(4) factor, a lysin motif domain containing protein, and a pentapeptide repeat protein. RNA-sequencing revealed fimbriae-related, flagella-related, and chemotaxis genes had increased expression in SX 245 compared to SX 244. Furthermore, SX 245 displayed higher invasion of human and bovine epithelial cells than SX 244. These data suggest that the presence and upregulation of genes involved in type 1 fimbriae production, flagellar regulation and biogenesis, and chemotaxis may play a role in the increased pathogenicity and host range expansion of the Salmonella Heidelberg isolates involved in the bovine-related outbreak.